Design and implementation of an efficient WPT system - Abdulkareem Mokif Obais; Ali Faeq Ruzij (Institute of Advanced Engineering and Science, 2020)
Wireless power transfer (WPT) is a technique introduced to transfer power wirelessly. Generally, WPT systems are characterized by low efficiency and low output power. Since WPT process depends mainly on mutual coupling between transmitting and receiving coils in addition to load requirements, it is focused in this work toward enhancing the mutual coupling and conditioning the receiving circuit so as to optimally satisfy the load demand. The mutual coupling between transmitting and receiving nodes is enhanced via inserting three resonating circuits along with energy transmission path and conditioning the receiving circuit such that it accomplishes delivering maximum power to the load node. In this work, an adaptive efficient WPT system is introduced. This system is carried out on PSpice and validated experimentally. Both simulative and experimental WPT systems have accomplished significant enhancement in efficiency. The proposed WPT system has three resonators and three parallel connected identical receiving coils located at 6.61m from the power transmitter. The efficiency enhancement approaches thousands of times the efficiency of a conventional WPT system having similar power transmitter located at the same distance from the receiving circuit, which has a single coil identical to those in the proposed efficient WPT system.